2009
DOI: 10.1016/j.molcel.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Lysine 56 Acetylation Is Linked to the Core Transcriptional Network in Human Embryonic Stem Cells

Abstract: Summary Lysine 56 acetylation in the helical core of histone H3 opens yeast chromatin and enables histone gene transcription, DNA replication, DNA repair, and prevents epigenetic silencing. While K56Ac is globally abundant in yeast and flies its presence has been uncertain in mammals. We show here using mass spectrometry and genome wide analyses that K56Ac is present in human embryonic stem cells (hESCs) overlapping strongly at active and inactive promoters with the binding of the key regulators of pluripotenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
171
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(188 citation statements)
references
References 44 publications
15
171
1
Order By: Relevance
“…Our previous work using Agilent microarrays found that histone H3K56ac is associated with upstream regulatory DNA sequences of the core transcriptional network in human ESCs (10). H3K56ac is conserved from yeast to mammals and is very abundant in yeast, marking ∼30% of total histone H3.…”
mentioning
confidence: 99%
“…Our previous work using Agilent microarrays found that histone H3K56ac is associated with upstream regulatory DNA sequences of the core transcriptional network in human ESCs (10). H3K56ac is conserved from yeast to mammals and is very abundant in yeast, marking ∼30% of total histone H3.…”
mentioning
confidence: 99%
“…Antifungal drug resistance is a major clinical problem, and few drugs are available to battle Candida infections (21). H3K56 acetylation appears to be much less abundant in mammals than in yeasts (22)(23)(24), and close homologs of Rtt109 are not detected outside of the fungal kingdom (25,26). Therefore, we hypothesized that Rtt109 might provide a unique target for antifungal therapeutics, and we began to investigate the importance of H3K56 acetylation in fungal pathogenicity.…”
mentioning
confidence: 99%
“…Rtt109 acetylates lysine 56 on the histone H3 core domain (H3K56), a mark that occurs globally on newly synthesized histones in Saccharomyces cerevisiae and Schizosaccharomyces pombe and is required for genome stability (13,15,(18)(19)(20)(21). H3K56ac was recently detected in humans, where it has been shown to be prominent in multiple cancers and is enriched at genes that are key regulators of stem cell pluripotency (22)(23)(24). H3K56ac is absent in yeast cells lacking Asf1 (asf1Δ mutants), indicating an essential role for Asf1 in the Rtt109-dependent acetylation of H3K56 (11,13,25).…”
mentioning
confidence: 99%